2008
DOI: 10.1111/j.1468-2257.2008.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

International Trade and the Changing Demand for Skilled Workers in High‐Tech Manufacturing

Abstract: States and localities in the U.S. put considerable effort into attracting and maintaining high-tech manufacturing industries to preserve manufacturing employment. However, little work has examined whether high-tech industries respond differently than traditional manufacturing to changing trade pressures. This study investigates the impact of international trade on skilled and unskilled labor demand across manufacturing sectors. Results of this study indicate that changes in exchange rates and trade orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…There is some variation in the literature regarding the definition of high technology industries and the measurement of R&D intensity. Our dummy variable definition spans a range of industries (28xx‐39xx) from the manufacturing sector (SIC division D) such that most of the industries in this range commonly appear in studies or have been identified in at least one study as being a high technology‐ or R&D‐intensive industry (see, e.g., Hecker, 1999; Cortright and Mayer, 2001; Silva, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…There is some variation in the literature regarding the definition of high technology industries and the measurement of R&D intensity. Our dummy variable definition spans a range of industries (28xx‐39xx) from the manufacturing sector (SIC division D) such that most of the industries in this range commonly appear in studies or have been identified in at least one study as being a high technology‐ or R&D‐intensive industry (see, e.g., Hecker, 1999; Cortright and Mayer, 2001; Silva, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, operational capability is particularly crucial for the high-tech sector because of its dynamism, uncertainty, and competitiveness. Specifically, for firms operating in a rapid-changing technology environment, agility, fast-adaptation, and quick response are critical for survival and prosperity (Gaulier et al , 2007; Lin et al , 2012; Silva, 2008). Due to their dynamic, uncertain and competitive operating nature, high-tech firms are often the pioneers in the adoption of administrative, operational, and information technology (IT) innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Working effectively with the suppliers can help to achieve cost competitiveness, customer responsiveness, and operational flexibility (Pagell and Krause, 2002;Kumar and Liu, 2005;Gunasekaran and Ngai, 2007;Steiner, 2008). Nowadays, the suppliers have become an important strategic partner because of their impacts on a company's financial performance (Rungtusanatham et al, 2003;Sarkis et al, 2007;Silva, 2008;Wu, 2009). In general, Talluri and Sarkis (2002), Garfamy (2003), and Green et al (2009) suggested that the success of supply-chain management depended on:…”
Section: Introductionmentioning
confidence: 99%